Effect of Exercise Methods and Eye-Hand Coordination on Forehand Drive Table Tennis Basic Technical Ability - Susetyorini, Jurit Tri; Rahayu, Tandiyo; Rahayu, Setya (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
This study was carried out based on the real problems. In fact, the training methods on extracurricular table tennis were still not optimal, due to the lack of training methods used, so that they were less effective without the targets obtained. The forehand drive technique is one of the basic techniques that is important in table tennis game. This study aims to determine the effectiveness of training methods and eye-hand coordination on basic engineering abilities. This study used an experimental method with Factorial Block 2x2 design. There is a significant difference between the results of the basic forehand technique of table tennis driveability training between students with high eye-hand coordination and students with low eye-hand coordination. Obtained an average value in the high eye-hand coordination group obtained 6.5 while the low eye-hand coordination obtained an average of 4.55, where Fvalue = 8.582 with a significance of 0.006. It turned out that the significance value obtained was less than 0.05. Based on data analysis, it can be concluded that there is an interaction effect between the training method of returning ball bait and the level of eye-hand coordination to the basic forehand ability of a table tennis drive.